Ground-penetrating radar for monitoring the distribution of near-surface soil water content in the Gurbantünggüt desert - Qin, Yanfang; Chen, Xi; Zhou, Kefa; Klenk, Patrick; Roth, Kurt; Sun, Li (Environmental earth sciences, 2013)
In the Gurbantünggüt Desert, snowmelt-induced high soil water contents briefly create favorable conditions for the germination and growth of plants every spring. Monitoring the rapidly changing conditions in this time period demands fast and efficient methods for measuring soil water contents at the field scale. For this study, a series of ground-penetrating radar (GPR) measurements were carried out on sites characterized by semi-vegetated dunes both in April 2010 and 2011. We compare water contents calculated from the GPR direct ground wave signal to both point scale validation measurements by time-domain reflectometry (TDR) and gravimetric sampling. Our results show that GPR is an effective method to rapidly obtain a detailed image of the field scale soil water content distribution in the Gurbantünggüt Desert with an accuracy similar to TDR. Observed large scale soil water content variations are dominated by dune topography: During snow melting, melt water was found to trickle slowly from the dune ridges to interdune valleys, increasing the soil water content there while the dune ridges quickly started to dry down. In dune valleys, smaller scale near-surface soil water content changes were dominated by variations in the vegetation coverage, leading to snowmelt funnels at distinct locations: The snowmelt initially occurred around the stems and branches of plants, forming funnel-shaped melt water induced holes through the snow cover and leading to an increasing amount of melt water collected around these plant roots. Our comparison of data from 2010 to 2011 furthermore suggests a temporally stable distribution of near-surface soil water content. This has important ecological significance for controlling desertification and for restoring and reconstructing vegetation in the Gurbantünggüt Desert.
Gesehen am 10.12.2021